The wage-productivity gap revisited: Is the labour share neutral to employment? - Marika Karanassou; Hector Sala (Queen Mary University of London, School of Economics and Finance, 2010)
This paper challenges the prevailing view of the neutrality of the labour income share to labour demand, and investigates its impact on the evolution of employment. Whilst maintaining the assumption of a unitary long-run elasticity of wages with respect to productivity, we demonstrate that productivity growth affects the labour share in the long run due to frictional growth (that is, the interplay of wage dynamics and productivity growth). In the light of this result, we consider a stylised labour demand equation and show that the labour share is a driving force of employment. We substantiate our analytical exposition by providing empirical models of wage setting and employment equations for France, Germany, Italy, Japan, Spain, the UK, and the US over the 1960-2008 period. Our findings show that the timevarying labour share of these countries has significantly influenced their employment trajectories across decades. This indicates that the evolution of the labour income share (or, equivalently, the wage-productivity gap) deserves the attention of policy makers.
Keywords: E24; E25; O47; 330; wages; productivity; labour income share; employment; Produktivität; Lohnniveau; Arbeitsangebot; Arbeitsnachfrage; Lohnquote; Lohnverhandlungen; Industriestaaten